1992
DOI: 10.1139/b92-293
|View full text |Cite
|
Sign up to set email alerts
|

Development of stigmatoid anthers in a tobacco mutant: implications for regulation of stigma differentiation

Abstract: We characterized the development of a tobacco floral mutant, Mgr27, previously obtained by selecting for resistance to an inhibitor of an enzyme in the polyamine biosynthetic pathway. Mgr27 plants are shorter than the wild type with smaller leaves and a compact inflorescence. The plants have a regular leaf plastochron and a vegetative shoot apex similar to the wild-type vegetative shoot apex. There are frequently more than five floral organs in the first three whorls, and the anthers produce stigmatoids. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Tobacco cell culture variants resistant to the inhibitor MGBG showed some floral abnormalities (e.g. Trull et al, 1992). More recently, Fritze et al (1995) repeated, and greatly improved, the tobacco culture mutant screen for resistance to MGBG, and found many of the same floral and vegetative phenotypes as we did (Malmberg and Rose, 1987).…”
Section: Introductionsupporting
confidence: 60%
“…Tobacco cell culture variants resistant to the inhibitor MGBG showed some floral abnormalities (e.g. Trull et al, 1992). More recently, Fritze et al (1995) repeated, and greatly improved, the tobacco culture mutant screen for resistance to MGBG, and found many of the same floral and vegetative phenotypes as we did (Malmberg and Rose, 1987).…”
Section: Introductionsupporting
confidence: 60%
“…Screening for resistance to the S ‐adenosylmethionine decarboxylase inhibitor methylglyoxal‐bis(guanylhydrazone) [22–24] or inhibitory concentrations of spermine [25], yielded mutants that showed reduced sensitivity to the respective agent, but these mutants have not been exploited for the analysis of polyamine function.…”
Section: Introductionmentioning
confidence: 99%
“…The leaf plastochron was variable from one plant to the next at the same leaf position, and there was no consistent pattern on individual plants. In wild type plants under the same growth cham ber conditions, the leaf plastochron varies between 1.23 ± 0.15 and 3.15 ± 0.29 (Trull, Holaway, and Malmberg, 1992). Puzzle box plants display helical phyllotaxy like wild type plants.…”
Section: Resultsmentioning
confidence: 97%
“…Hill and Malmberg (1991) reported that wild type tobacco produces 21 to 24 leaves prior to flowering under greenhouse conditions and that the leaf plastochron for vegetative shoots gradually decreases as flowering approaches. Under 24 C growth chamber conditions, wild type plants produce 20 to 23 leaves before flowering and the leaf plastochron gradually decreases as flowering approaches (Trull, Holaway, and Malmberg, 1992). The puzzle box vegetative meristem produces a variable number of small leaves at irregular intervals, and the leaf plastochron does not decrease as flowering approaches.…”
Section: Discussionmentioning
confidence: 99%